Artificial Intelligence Literacy and Teachers' Readiness in EFL Context: A Systematic Literature Review - Ni Luh Putu Anis Darma Wulan; Made Hery Santosa (Journal of English Language Teaching, Linguistics, and Literature (JETLEE), 2026)
Existing studies on AI literacy have largely focused on students, leaving EFL teacher preparedness underexplored. This study aims to explore the level, determinants, barriers, and recommended solutions regarding AI literacy and EFL teachers’ readiness. Using the SLR method with PRISMA guidelines and Lame’s (2019) framework, this synthesized six empirical articles published between 2022 and 2025 from the Google Scholar database. The findings report that AI literacy and EFL teachers’ readiness are classified at a moderate level. The majority of determinants include internal and external factors. Next, this study identified significant barriers such as limited infrastructure, lack of professional development training, ethical concerns, and AI anxiety. To address these challenges, recommended strategies include continuous professional development based on the AI-TPACK framework, the formulation of clear institutional ethics policies, and the adoption of peer mentoring models. Ultimately, there is a strong positive correlation between AI literacy and teacher preparedness. This study provides a foundational framework to assist educational institutions in designing future-ready professional competency standards for EFL educators.